2020
DOI: 10.3390/technologies8020035
|View full text |Cite
|
Sign up to set email alerts
|

Unsupervised Domain Adaptation in Semantic Segmentation: A Review

Abstract: The aim of this paper is to give an overview of the recent advancements in the Unsupervised Domain Adaptation (UDA) of deep networks for semantic segmentation. This task is attracting a wide interest since semantic segmentation models require a huge amount of labeled data and the lack of data fitting specific requirements is the main limitation in the deployment of these techniques. This field has been recently explored and has rapidly grown with a large number of ad-hoc approaches. This motivates us to build … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(67 citation statements)
references
References 116 publications
0
58
0
Order By: Relevance
“…Recently, auxiliary tasks, such as the adaptation of a well-trained model from a similar domain with a similar task [11], [41], have been leveraged to migrate this problem. Although we will not cover the unsupervised segmentation and their solutions, such as unsupervised domain adaptation (UDA) [42] and zero-shot learning [43], we mention it here to start by looking at all settings in the big picture. In this paper, we focus on methods that learn to segment medical images with incomplete, inexact, and inaccurate annotations by jointly leveraging a few labeled data and a large number of unlabeled examples.…”
Section: Image Segmentation With Limited Supervisionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, auxiliary tasks, such as the adaptation of a well-trained model from a similar domain with a similar task [11], [41], have been leveraged to migrate this problem. Although we will not cover the unsupervised segmentation and their solutions, such as unsupervised domain adaptation (UDA) [42] and zero-shot learning [43], we mention it here to start by looking at all settings in the big picture. In this paper, we focus on methods that learn to segment medical images with incomplete, inexact, and inaccurate annotations by jointly leveraging a few labeled data and a large number of unlabeled examples.…”
Section: Image Segmentation With Limited Supervisionmentioning
confidence: 99%
“…Thus, pretraining on relevant domains and applying to the current domain with supervised or semi-supervised training, known as Domain Adaptation [219] or Domain generalization, has received growing attention. Please refer to [42] for comprehensive reviews of domain adaptation for semantic segmentation.…”
Section: K Summarymentioning
confidence: 99%
“…In this section, we will give a brief review of related works in both areas. A more detailed review of UDA for image segmentation can be found in [18]- [22]. In the field of UDA, early research mainly focused on aligning the distributions of feature space by minimizing distance measurements.…”
Section: Related Workmentioning
confidence: 99%
“…However, such global feature alignment does not necessarily result in the intraclassly correct semantic representation of the target domain. 29 In multiple class segmentation, it almost fails to achieve substantial gains over the baseline that is trained with data augmentation and registration. 42 For some small-gap UDA tasks of medical image segmentation, the generative-based approaches are wildly used.…”
Section: Introductionmentioning
confidence: 99%